2022
DOI: 10.1007/s00520-022-07556-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of shared decision making in oncology within the United States: a scoping review

Abstract: Purpose Shared decision making (SDM) among the oncology population is highly important due to complex screening and treatment decisions. SDM among patients with cancer, caregivers, and clinicians has gained more attention and importance, yet few articles have systematically examined SDM, specifically in the adult oncology population. This review aims to explore SDM within the oncology literature and help identify major gaps and concerns, with the goal to provide guidance in the development of clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Our study reiterates those findings and also highlights the possibility of text summaries becoming “a voice” for older adults during consultations with their clinicians. Text summaries allow for better and more streamlined conversations with clinicians, thereby promoting shared decision-making [ 56 , 57 ]. It is important to note that the preferences and recommendations of our participants informed revisions of the app features and functionalities in the prototype iterations, and the current state of the app reflects the needs of its potential users.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reiterates those findings and also highlights the possibility of text summaries becoming “a voice” for older adults during consultations with their clinicians. Text summaries allow for better and more streamlined conversations with clinicians, thereby promoting shared decision-making [ 56 , 57 ]. It is important to note that the preferences and recommendations of our participants informed revisions of the app features and functionalities in the prototype iterations, and the current state of the app reflects the needs of its potential users.…”
Section: Discussionmentioning
confidence: 99%
“…However, the levels of cancer literacy vary from country to country and region to region, and some populations lack systematic information about cancer treatment 13 . It has also been suggested that inequalities in the shared decision‐making (SDM) process among patients of different racial and ethnic backgrounds affect the quality of healthcare they receive 14 . Several barriers to SDM in oncology have been identified, including uncertainty in the treatment decision, concerns regarding adverse effects, and poor physician communication 15 .…”
Section: Introductionmentioning
confidence: 99%
“…For Patients, their treatment priorities and desired outcomes must guide treatment decisions and their modifications. Patient preferences, shared decision making, 7 and patient-reported outcomes are well known, beneficial con-cepts, but are not yet fully implemented in clinical practice. 8 Patient preferences are also key elements of patient-centered care and deserve a prominent place in the EHR.…”
Section: Introductionmentioning
confidence: 99%